Shaping Future Engineers Inquiry-Based Learning with Generation Z Curiosity and Critical Thinking - Mahanty, Chandrakanta; Manjeti, Vijaya Bharathi; Bollapragada, Suraj Aravind; Mahanthi, Bangaru Lakshmi; Sarojini Devi, S.; Tripathy, Shibani (Journal of Engineering Education Transformations, 2026)
The dominant population in engineering classrooms today is Generation Z students who are highly digitally fluent, collaborative in learning styles, and interactive in their learning activities. Traditional pedagogies of lectures often fail to keep them engaged and develop higher-order thinking, while inquiry-based learning has emerged as a promising alternative. Despite the growing interest in IBL, limited empirical research has investigated how curiosity and critical thinking together influence students’ perceived effectiveness of IBL in engineering education. This quantitative study used a survey approach with 500 engineering students in the age group of 18-21 years, using a 26-item Likert-scaled instrument that measured curiosity, critical thinking, IBL effectiveness, and learning preferences. The scales demonstrated strong internal consistency through Cronbach’s alpha values which ranged between 0.88 and 0.95. The correlation and regression analyses revealed curiosity and critical thinking as statistically significant predictors of IBL effectiveness with r = 0.799 and 0.755, respectively, jointly explaining 64 percent of the variance, while experience with IBL accounted for an insignificant amount of variation. Student engagement and perceived learning effectiveness stem from their natural curiosity and reasoning abilities instead of their knowledge of the method. The research suggests that engineering programs should develop Generation Z students’ cognitive skills through inquiry-based teaching methods which combine technology and reflection because these students need these competencies to succeed in our fast-paced world.